UNDERSTANDING WOOD FINISHING USING THE JAPANESE WOOD BURNING TECHNIQUE (SHOU SUGI BAN) IN ARCHITECTURE - Ni Luh Kadek Resi Kerdiati (Yayasan Sinergi Widya Nusantara, 2021)
Purpose : This study aims to give insights regarding Shou Sugi Ban to a degree that becomesknown to more people.Research methods : Applies a literature study method that works by analyzing the data collected.The source of the data is mostly taken from journals, research articles, books, and online websites.Findings : Shou Sugi Ban is a Japanese technique of finishing wood by charring the surface withfire. This technique is environmentally friendly because it naturally makes the wood impossible toabsorb moisture so that the wood can be protected from termites and mold. Generally, there are fivesteps to a perfect Shou Sugi Ban: (1) materials preparation, (2) burn process, (3) surface prep orsanding, (4) stain process, (5) finish process. In architecture, this wood finishing is appropriate forexterior and interior.Implications : The information provided is to be able to add insight and knowledge about one of thenatural finishing techniques that still looks beautiful but is environmentally friendly. So later, theadvantages of finishing Shou Sugi Ban can be more widely known and utilized in the development ofarchitecture.